Islamic Macro Economy: A New Paradigm - Ade Khadijatul Z. HRP; M. Shabri Abd. Majid; Rahmat (International Journal of Economics (IJEC), 2023)
This study seeks to explore Islamic macroeconomics as a new paradigm and its application in controlling inflation, monetary and fiscal in conventional and Islamic macroeconomics. Then explore some points about the development of macroeconomics at the time of the Prophet Muhammad. The approach method used in this study is descriptive qualitative analysis, with library research data collection techniques using secondary data in accordance with a number of relevant literature. Then the data analysis technique was carried out by inductive deductive techniques. The results show that monetary policy is an important instrument of political policy in the economic system, both conventional and Islamic and this policy has existed and began to develop since the time of the Prophet Muhammad. The fundamental difference between Islamic and conventional macroeconomics lies in the purpose and prohibition of interest in Islam, the condition for achieving and ensuring the proper functioning of the monetary system is that the monetary authority must supervise the entire system. Monetary policy and fiscal policy are macroeconomic policies that are very important in relation to achieving inflation targets and economic growth. Therefore, in an effort to overcome inflation, monetary and fiscal policies, the government can carry out various macroeconomic policies to achieve inflation targets and economic growth.